Cytotoxic saponin poliusaposide from Teucrium polium1. Issue 34 (15th April 2015) - Elmasri, Wael A.; Hegazy, Mohamed-Elamir F.; Mechref, Yehia; Paré, Paul W.
<x xml:space="preserve">Abstract</x> Three saponin glycosides have been isolated and characterized from Teucrium polium L. (Lamiaceae).